orms of public education policy in the 19th century - Balla, János (Church History Review, 2025)
From the end of the 17th century, the philosophers of the Enlightenment set in motion a drive to separate church and state affairs in European states. We cannot talk about a theoretical, clear-cut separation in any country at any point. This can be clearly seen in the field of education, where almost all the states studied came to the idea through the intermediary of a religious institution, in one way or another, that they too should be involved in the education of their citizens. The common feature of the evolving modern European public education systems is that almost none of them reach the idea of compulsory, state-supervised education until the end of the 19th century – sometimes the beginning of the 20th century – and that the elementary and secondary levels of national public education are separated systems. In the resulting, basically dual school system, the different types of institutions set different educational objectives and use specific teaching methods to achieve these. The supervisory and institutional governance systems of the two systems are also different. The people’s school, which is compulsory for all citizens, focuses on teaching basic skills (reading, writing, arithmetic) and “acquiring” a sense of national identity.